Fire resistance of ECC materials - Toh, Elaine Siock Hui (2015)
A fire attack is one of the most severe conditions that a structure can be subjected to. Its consequence is not limited to damages on structural components but also on the livelihood of people use the facility. Engineered cementitious composites (ECC) are a relatively new concrete material that incorporates fibres in the mix design. It is considered a more environmentally friendly substitute to normal concrete because of the partial replacement of cement content with waste materials such as fly ash. One of its characteristics is the high ductility, which is the reason behind the name 'bendable concrete'. In terms of sustainability, this type of concrete is likely to have a potential market in the future due to its many beneficial characteristics. However, there are limited researches in the area of fire resistance of ECC. In this study, an experimental programme had been set up to study the effects of design parameters, such as water/binder ratio; fly ash (FA) replacement ratio, sand/binder ratio, addition of steel fibres to polyvinyl alcohol(PVA) fibre - ECC; ground-granulated blast-furnace slag (GGBS) and FA replacement ratio. These parameters were studied as the available materials in the laboratory were not similar, in terms of material properties, as compared to research papers. In addition, a new set up for direct tension test was devised to reduce the limitations of the existing set up. In total there were 9 mixes used to evaluate on the above stated parameters on the performance of ECC. After which, one mix that exhibited relatively well tensile stress and strain was chosen to be used for conducting of fire tests. 4 types of fire tests were carried out to determine the effect of fire on the local PVA-ECC. They are 3-hour spalling test, 2-hour spalling test, hot strength test and cold strength test. It was found that the mix with the lowest w/b ratio exhibited better tensile stress-strain relationship and therefore it was chosen for the fire test. After conducting the spalling tests for the local PVA-ECC, there was no observable spalling or cracks. It was deduced that PVA fibre might have helped in relieving the pressure and stress within the concrete by creating channels for these pressures to escape. In the hot strength test, 74.6% residual strength was obtained and even after the compressive strength test, the cylinder specimen remained intact. It was concluded that ECC exhibits potential fire resistance characteristics but more researches should still be conducted to ensure the consistency in results.